Hydrogel nanomembranes as templates for patterned deposition of nanoparticles on arbitrary substrates - Meyerbröker, Nikolaus; Zharnikov, Michael (ACS applied materials & interfaces, 2014)
Patterns of nanoparticles (NPs) on solid supports are usually restricted to a particular substrate or a class of substrates. Here we present a procedure that decouples the patterning step from the target substrate, enabling the fabrication of custom designed NP assemblies on nearly any solid support, including nonflat ones. The procedure relies on a hydrogel template prepared on the primary, conductive substrate and transferred to the target support as a sacrificial nanomembrane. The template is structured by electron beam lithography (EBL) which seals predefined areas of poly(ethylene glycol) based hydrogel film, making them inert to NP deposition in contrast to pristine areas that adsorb NPs in high densities. The deposition of NPs, occurring from an aqueous solution into the transferred membrane, follows EBL generated structure, delivering the desired NP pattern on the target support after removal of the organic matrix. Efficiency and flexibility of the procedure is illustrated by creating a variety of representative submicrometer patterns of densely packed gold and silver NPs on glass, including a useful pattern of a miniaturized quick-response code. The arrangement of NPs in these patterns corresponds to the negative image of EBL generated template. This significantly reduces the exposure time for designs where large areas covered with NPs are separated by thin, NP-free stripes.
Gesehen am 28.07.2020